A multi-functional SiO32−-releasing hydrogel with bioinspired mechanical properties and biodegradability for vascularized skeletal muscle regeneration. Issue 37 (6th May 2022) - Xu, Pengcheng; Yang, Qiang; Zhang, Lin; Wu, Kang; Bai, Yanjie; Saijilafu; Yang, Huilin; Zhou, Huan; Lin, Xiao; Yang, Lei
Abstract : A SiO3 2− -releasing hydrogel (SRH) demonstrates multiple functions for skeletal muscle regeneration. The SRH with bioinspired biodegradation behavior enhances vascularized muscle regeneration. Abstract : Vascularized skeletal muscle regeneration remains a great medical need but significant challenge. Biomaterial strategies that can facilitate the regeneration of muscle fibers and blood vessels are unavailable. Herein, we report a new cell- and drug-free biomaterial-based strategy for the repair of severely injured skeletal muscles. A novel multi-functional silicate ion-releasing hydrogel (SRH) was developed by dissolving PVA and starch in Na2 SiO3 solutions, followed by freeze–thawing treatment. The mechanical properties and degradation profile of the SRH could be easily adjusted by altering the amylose/amylopectin ratio of starch. The SRH efficiently releases silicate ions to create a favorable microenvironment for enhanced skeletal muscle repair, while the mechanical properties and biodegradability of SRHs is adjusted to match the muscle regeneration environment. Silicate ions released from the SRH simultaneously promote myoblast proliferation and myogenic differentiation, decrease oxidative stress, and enhance the angiogenesis of vascular endothelial cells in vitro . Silicate ions released from the SRH scaffold with bioinspired mechanical properties and biodegradability promote the de novo formation of muscle fibers and blood vessels while inhibiting tissue fibrosis, leading to enhanced vascularized muscle regeneration in vivo . With multiple biofunctions and mechanical/degradation tunability, the SRH platform bears great potential in the skeletal muscle tissue engineering and treatment of formidable clinical problems such as volumetric muscle loss and sarcopenia.